Volume 8: Energy 2020
DOI: 10.1115/imece2020-24356
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effects of Convective Heat Transfer on Photovoltaic Performance and Optimal Tilt Angle

Abstract: Electrical performance of photovoltaic (PV) cells are affected by their operating temperatures, which lead to changes in the performance of the PV panel. The performance and efficiency of a PV system is dependent upon many factors, such as its angle of incidence, accumulation of dust, speed and direction of natural winds. Particularly, angle of incidence between solar rays and PV modules is the most important. This paper will focus on developing a numerical tool for predicting the optimal tilt angle, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Jaffery et al (2018) proposed a method to characterize the operating temperature of the PV panel under outdoor conditions using thermal imaging [19]. Wu et al (2018) performed wind tunnel experiments and computational fluid dynamics (CFD) simulations to investigate the temperature distribution on a PV panel, and the results of this study were used by Ghabuzyan et al (2020) [20,21]. Al-Waeli et al (2019) discussed the existing evaluation criteria for PV/T, suggested four novel methods, and outdoor experiments were done in Bangi-Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Jaffery et al (2018) proposed a method to characterize the operating temperature of the PV panel under outdoor conditions using thermal imaging [19]. Wu et al (2018) performed wind tunnel experiments and computational fluid dynamics (CFD) simulations to investigate the temperature distribution on a PV panel, and the results of this study were used by Ghabuzyan et al (2020) [20,21]. Al-Waeli et al (2019) discussed the existing evaluation criteria for PV/T, suggested four novel methods, and outdoor experiments were done in Bangi-Malaysia.…”
Section: Introductionmentioning
confidence: 99%